A Case of COVID-19 Pregnancy Complicated with Hydrops Fetalis and Intrauterine Death - Daniela Eugenia Popescu; Andreea Cioca; Cezara Muresan; Dan Navolan; Arina Gui; Ovidiu Pop; Tamara Marcovici; Constantin Ilie; Marius Craina; Marioara Boia (Medicina, 2021)
Coronavirus disease 2019 (COVID-19) has rapidly evolved into a worldwide pandemic causing a serious global public health problem. The risk of vertical transmission of SARS-CoV-2 is still debated, and the consequences of this virus on pregnant women and their fetuses remain unknown. We report a case of pregnancy complicated with hydrops fetalis that developed 7 weeks after recovery from a mild SARS-CoV-2 infection, leading to intrauterine death of the foetus. Evidence of SARS-CoV-2 placentitis was demonstrated by the presence of viral particles in the placenta identified by immunohistochemistry. As we excluded all possible etiological factors for non-immunologic hydrops fetalis, we believe that the fetal consequences of our case are related to vertical transmission of SARS-CoV-2 virus. To the best of our knowledge, this is the second reported case in the literature of COVID-19 infection complicated with hydrops fetalis and intrauterine fetal demise.